FALSIFICATION OF HISTORY IN THE DIGITAL AGE: CHALLENGES AND THREATS - Bektashev Rishat Farxadovich (Uzbekistan Open Conference, 2026)
The article analyzes the transformation of mechanisms for falsifying historical memory in the context of the transition to a digital society. Such phenomena as deepfakes, algorithmic bias in search engines, the viral spread of historical myths on social networks, and the use of generative neural network technologies for revising the past are examined. The key challenges for the professional historical community are identified, including the blurring of source criticism criteria, the erosion of trust in archives, and the acceleration of “digital amnesia.” In conclusion, institutional and technological measures to counter these threats are proposed.
Keywords: falsification of history; digital era; historical memory; deepfake; manipulation of consciousness; source studies; information security